The Exegetical and the Ethical : The Bible and the Academy in the Public Square. Essays for the Occasion of Professor John Barton's 70th Birthday - Clifford, Hywel; Daffern, Megan (Biblical Interpretation Series, 2022)
Exegesis has ethical dimensions. This is the case for the Bible, which has a foundational status in traditional perspectives that is simultaneously contested in the modern world. This innovative essay collection, largely about Hebrew Bible/Old Testament texts, is written by an international team - all Doktorkinder of a pioneer in this area, Professor John Barton, whose 70th birthday this volume celebrates. With interdisciplinary angles, the essays highlight the roles and responsibilities of the biblical scholar, often located professionally between religious and secular domains. This reflects a broader reality: all readers of texts are engaged ethically in the public square of ideas.